Comunidades ciganas da Bahia e de Pernambuco: léxico, cultura e sociedade - Silva, Geysa Andrade da (2017)
The lexicon is a dynamic and flexible repertoire of words which many theorists have examined. For being quite diverse, it has a considerable potential for research and although it is far from exhaustion, all production has been very promising. According to Oliveira and Isquerdo (2001), even if the window through which a community can see the world is an abstract unit, it is possible to construct a verifiable rational and systematic knowledge, that is science, of its elements. From the need to explore this lexical inventory, the following question has been developed: do the lexical items produced provide data that mark the lexical variation of the gypsies? The research demanded an investigation in loco in cities of Bahia (Miguel Calmon and Jacobina – Meso-region of the Center-North of Bahia) and of Pernambuco (Flores and Ouricuri – Meso-region of Pernambuco’s Sertão) from which the diatopic variation identified in sample data can be demonstrated. Respondents, men and women of different age groups - for diagenetic and diagenerational variation - gypsies, as well as other social information, responded to the structured instrument, excerpt of Semantic-Lexical Questionnaire of Linguistic Atlas of Brazil – ALiB, specifically six questions of the semantic area of Games and children's recreation, through which it was tried to document the variation of the most general denominations of use or other specific denominations of the group. From the analysis of this corpus, the lexical contributions that mark the identity of the gypsy people were identified and the extra linguistic conditioners that influence the lexical realization of the gypsy community were verified. Linguistic factors, although conditioning factors of the variation, were not object of study in this work, they proved, therefore, inappropriate for the lexical level in question. The course with the gypsy groups drew restrictions at the questionnaire level, just as the Ethics Committee required the release of enough energy. The methodology and procedures are based on those adopted by ALiB. A lexicon search aims to determine the origin, form, and meaning of the words that make up the collection of a language; the one proposed here is based on analysis of Lexicology, Sociolinguistics and Dialectology since it aims to observe the use of the word in the community of speakers. The results indicate that the lexical variation is basically a result of the region where the speaker is inserted, and sometimes other variations due to age, sex, educational level, and not ethnicity.